SCIENTIFIC VALIDATION OF SASTRIC SIDDHA DRUG MANJAL KAMALAI KIYAZHAM AGAINST PARACETAMOL INDUCED HEPATOTOXICITY IN ZEBRA FISH (DANIO RERIO) MODEL - R, GOMATHI; E, PREETHEEKHA; PRIYA P, SHANMUGA; A, MAMALLAN (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The objective of this study is to assess the hepatoprotective nature of Siddha formulation manjal noi kudineer (MNK) against Paracetamol induced hepatotoxicity in Zebrafish Danio rerio model. Methods: Pharmacological studies were carried out in the adult zebra fish model in the category of four groups; each individual group contained ten animals. Groups 1, 2, 3, and 4 were considered as control groups, disease control groups, and drug treated groups at different concentrations, respectively. Histopathological analysis was recorded. Results: The observed research findings were confirmed that this novel Siddha formulation MNK possess potent hepatoprotective effect at the both dose level of 250 mg/l–500 mg/l against paracetamol induced toxicity in Zebrafish. Conclusion: Siddha medicinal formulation has been in practice for more than 1000 years. Liver diseases are the highly prevalent one among all the diseases. Although huge drugs are available for liver diseases, there is a need for cost effectiveness drugs without any adverse effect. From the study, it was concluded that the drug MNK has promising hepatoprotective activity in dose-dependent manners and restores the basic liver architecture by means of its rejuvenating potential against paracetamol induced toxicity in Zebrafish model. We can strongly suggest that the Sastric Siddha drug MNK to treat various kinds of liver diseases such as liver cirrhosis and hepatic carcinoma. This research work may be highly beneficial to the people who suffered from various liver diseases if the drug will be given clinically.